Connecting to belonging: a cross-disciplinary inquiry into rural Australian Anglican Church engagements with people from culturally and linguistically diverse backgrounds. Issue 1 (2nd January 2017) - Short, Monica; Broughton, Geoff; Short, Mark; Ochala, Yangi; Anscombe, Bill
Abstract: People from diverse backgrounds enrich the rural, regional, and remote communities where they relocate and settle. Research about rural diversity tends to focus on demographics (age, gender, country of origin) while ignoring personal narratives of integration, for example, engagements with religious institutions (such as the local Christian church). This article presents the research themes from an investigation using co-operative inquiry into rural diversity and the Anglican Church, with specific reference to the Australian experience. It is a cross-disciplinary dialogic exchange between social workers and theologians. Positive narratives about connection, welcome, participation, and belonging are shared.